2009
DOI: 10.1007/s00417-009-1120-8
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent tamponade by room air as compared with SF6 after macular hole surgery

Abstract: This study suggests that room air may have an equivalent tamponade effect, in spite of the shorter prone positioning period, than SF(6) after MH surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 28 publications
2
46
0
1
Order By: Relevance
“…At first, Park et al used air tamponade with 4 days prone positioning and observed hole closure in 91 % (Park et al, 1999). A closure rate over 90 % has been reported using air, including our previous report (Hasegawa et al, 2009;Hikichi et al, 2011;Sato et al, 2003). The recent views concerning management after macular hole surgery can be divided into two general approaches.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…At first, Park et al used air tamponade with 4 days prone positioning and observed hole closure in 91 % (Park et al, 1999). A closure rate over 90 % has been reported using air, including our previous report (Hasegawa et al, 2009;Hikichi et al, 2011;Sato et al, 2003). The recent views concerning management after macular hole surgery can be divided into two general approaches.…”
Section: Discussionmentioning
confidence: 97%
“…In our previous study, hole diameter was the most important prognostic factor among them (Hasegawa et al, 2009). And, the high closure rates were recently achieved regardless of tamponade material, so, there are many reports regarding the selection of tamponade material and the necessity of positioning restrictions after macular hole surgery.…”
Section: Fig 1 Scheme Of the Isolation Theory Rpe; Retinal Pigmentmentioning
confidence: 96%
See 3 more Smart Citations